Disrupted immune senescence in early pregnancy is associated with recurrent pregnancy loss - Parvanov, Dimitar; Ganeva, Rumiana; Ruseva, Margarita; Handzhiyska, Maria; Jelezarsky, Lachezar; Safir, Jinahn; Metodiev, Dimitar; Stamenov, Georgi; Hadjidekova, Savina (Frontiers in Immunology, 2026)
BackgroundImmune system adaptation plays a crucial role in pregnancy success. Cellular senescence, linked to immune dysfunction and chronic inflammation, may contribute to adverse pregnancy outcomes but remains poorly characterized during early gestation, at the systemic level.ObjectiveTo characterize senescence marker expression in peripheral leukocyte subsets in early pregnancy and to examine its association with miscarriage history and functionally distinct T helper cell populations.MethodsThis cross-sectional study included 52 pregnant women: 18 with recurrent pregnancy loss (≥2 miscarriages), 18 with one prior loss, and 16 controls with no loss history. Peripheral blood leukocytes were analyzed using an automated hematology analyzer and by flow cytometry for senescence markers (p16, p21, p53) and major T-cell subsets. Group differences were tested by ANOVA or Kruskal–Wallis test, as appropriate and exploratory Spearman correlation analyses examined associations between miscarriage number, senescent subsets, and T-cell populations.ResultsSenescent cells were detected as percentages of granulocytes, monocytes, and lymphocytes, with granulocytes exhibiting the highest senescence expression. A consistent p21>p16>p53 expression pattern across immune subsets was observed in controls, suggesting a physiologic senescence hierarchy. This organization was progressively disrupted in miscarriage groups. A stepwise increase with miscarriage number was observed across subsets. Significant differences were observed in the median percentage of p16+ monocytes between controls, one prior loss and RPL patients (0.20%, 0.41%, and 0.57%, respectively; p = 0.03). Corresponding increases were also detected for p16+ lymphocytes (0.06%, 0.17%, 0.35%; p < 0.01), p21+ granulocytes (0.78%, 5.75%, 11.7%; p = 0.04), and p53+ granulocytes (4.01%, 7.05%, 8.35%; p = 0.05). Spearman analyses supported these trends and further revealed positive associations between p16+ monocytes and Th17 cells and between p53+ granulocytes and Th1 cells (p < 0.05).ConclusionPregnancy loss history is associated with both quantitative and qualitative alterations in immune senescence profiles, including organizational remodeling of peripheral immune senescence. Analysis of proinflammatory and regulatory T-cell subsets revealed additional associations, suggesting immune senescence may interact with adaptive immune polarization in early pregnancy. These findings highlight disrupted immune senescence as a potential component of immune maladaptation and identify senescent immune cells as candidate biomarkers for recurrent miscarriage.